(untitled) (International Journal of Innovative Technologies in Economy, 2020)
The formation of the concept of knowledge management in the system of modern universities and educational production processes and the improvement of the quality of modern education necessitate the development of new integrated structures acting in accordance with the dynamic changes in the functioning of the economic education system and aimed at integration with other scientific structural divisions.Development in the domestic scientific and technical sphere is influenced by the limited use of innovations in the commercial activities of firms and companies, as an important component of the economic system, which requires the development of a set of measures and the creation of specialized infrastructural facilities that increase the effectiveness of the transfer of scientific research.